A consistency test of white dwarf and main sequence ages: NGC 6791 - García Berro, E. (2013)
NGC 6791 is an open cluster that it is so close to us that can be imaged down to very faintluminosities. The main sequence turn-off age (∼8 Gyr) and the age derived from the cut-off of the white dwarf luminosity function (∼6 Gyr) were found to be significantly different. Here we demonstrate that the origin of this age discrepancy lies in an incorrect evaluation of the white dwarf cooling ages, and we show that when the relevant physical separation processes are included in the calculation of white dwarf sequences both ages are coincident